2020
DOI: 10.3889/oamjms.2020.3796
|View full text |Cite
|
Sign up to set email alerts
|

Phytochemical Screening, Gas Chromatography-mass Spectrometry Analysis, and Antidiabetic Effects of Corchorus olitorius Leaves in Rats

Abstract: BACKGROUND: Therapies for diabetes mellitus are still meeting failure in most cases, especially in the developed stages of the disease due to incredible associating complications. Hence, there is a need for continuous development of curative therapies for that stubborn disease. AIM: We aimed to investigate the antidiabetic effects of one of the most popular plants cultivated in Egypt, C. olitorius. METHODS: Phytochemical screening of total alcoholic extract of Corchorus olitorius leaves and its aqu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…As shown in Figure 1B, 2,3-DCA exhibited an inhibitory effect on violacein production in C. violaceum CV026, while the minimum inhibitory concentration (MIC) of the 2,3-DCA against C. violaceum CV026 was determined to be over 500 µg/mL. Although 2,3-DCA is a common cinnamic acid derivative, to the best of our knowledge, only its ability to promote the formation of long and entangled wormlike micelles has been reported to date [19,20]. The isolation of 2,3-DCA from N. metallicus and its QS inhibitory effects on C. violaceum have not been reported.…”
Section: Isolation and Structural Elucidation Of Qsis From N Mentalli...mentioning
confidence: 96%
“…As shown in Figure 1B, 2,3-DCA exhibited an inhibitory effect on violacein production in C. violaceum CV026, while the minimum inhibitory concentration (MIC) of the 2,3-DCA against C. violaceum CV026 was determined to be over 500 µg/mL. Although 2,3-DCA is a common cinnamic acid derivative, to the best of our knowledge, only its ability to promote the formation of long and entangled wormlike micelles has been reported to date [19,20]. The isolation of 2,3-DCA from N. metallicus and its QS inhibitory effects on C. violaceum have not been reported.…”
Section: Isolation and Structural Elucidation Of Qsis From N Mentalli...mentioning
confidence: 96%
“…It has been reported that alcoholic and chloroform extracts of C. olitorius (100 mg/kg) protected against diabetic complications such as hyperlipidemia and determinant effects on the liver tissue. These pharmacological effects are due to the presence of some bioactive phytochemical constituents such as theophylline, trans-2, 3-dimethoxycinnamic acid, 7-hydroxy-4-methyl coumarin, apigenin 7-glucoside, and glycitein [ 128 ].…”
Section: Biological Activitymentioning
confidence: 99%